Escalated aggressive behaviour and facultative parental care in the nest building gladiator frog, Hyla faber - Martins, Marcio [UNESP]; Pombal Jr., José P.; Haddad, Célio F.B. [UNESP] (De Gruyter, 1998)
Agonistic encounters and facultative parental care in Hyla faber were observed in two localities in southeastern Brazil. Maximum male density was 0.9 and 3.3 males/m2 in Campinas and Ribeirão Branco, respectively. Aggression was escalated and the highly variable aggressive calls were specific to each phase of the encounter. The last, more aggressive phases rarely occurred in Campinas; in Ribeirão Branco they occurred frequently. Male parental care (egg attendance) was common in Ribeirão Branco while it was never observed in Campinas. Egg attendance lasted one to two nights and was observed only during high male density. The main benefit of egg attendance seemed to be avoiding nest intrusion by other males (sunken eggs and/or embryos invariably die). Males may build additional nests during egg attendance, but attending males did not attract females (they did not call).
Keywords: aggression; agonistic behaviour; calling; gladiator frog; nest building; parental care; Brazil, Sao Paulo State, Campinas; Brazil, Sao Paulo State, Ribeirao Branco; Hyla faber